The Instant Effects of Continuous Transcutaneous Auricular Vagus Nerve Stimulation at Acupoints on the Functional Connectivity of Amygdala in Migraine without Aura A Preliminary Study - Luo, Wenting (Neural plasticity, 2020)
Copyright © 2020 Wenting Luo et al.